The Other Quiet Professionals Lessons for Future Cyber Forces from the Evolution of Special Forces - Paul, Christopher (RAND Corporation, 2014)
With the establishment of U.S. Cyber Command, the cyber force is gaining visibility and authority, but challenges remain, particularly in the areas of acquisition and personnel recruitment and career progression. A review of commonalities, similarities, and differences between the still-nascent U.S. cyber force and early U.S. special operations forces, conducted in 2010, offers salient lessons for the future direction of U.S. cyber forces.